Analytical validation of ONCURIA™ a multiplex bead-based immunoassay for the non-invasive bladder cancer detection - Furuya, Hideki (Pract Lab Med, 2020)
BACKGROUND: The objective of our study was to assess the analytical performance of a multiplex assay (Oncuria™) to quantify protein biomarkers towards a bladder cancer associated diagnostic signature in voided urine. METHOD: ology: Using Luminex xMAP technology, a custom immunoassay was developed to measure the concentrations of 10 urinary analytes (angiogenin, ANG; apolipoprotein E, APOE; alpha-1 antitrypsin, A1AT; carbonic anhydrase 9, CA9; interleukin 8, IL8; matrix metallopeptidase 9, MMP9; matrix metallopeptidase 10, MMP10; plasminogen activator inhibitor 1, PAI1; syndecan 1, SDC1; vascular endothelial growth factor, VEGF). Selectivity, sensitivity, specificity, precision, linearity, dynamic range, and detection threshold were assessed using recombinant proteins and human urine samples. Analytical variability with respect to batch size, run, day, operator, and interference were also evaluated. RESULTS: Analytical evaluation demonstrated a) all antigen cross-reactivity was noted to be <1% of the tested concentration, b) minimal detected dose ranged from 0.295 ​pg/mL in IL8 to 31.1 ​pg/mL in APOE, c) highly reproducible and accurate noting coefficient of variation (CV) and relative error (RE) values below 15% for all analytes and d) minimal interference. The assay can be completed in <5 ​h using as little as 150 ​μL of voided urine. CONCLUSION: To our knowledge, this is the first multiplex bead-based immunoassay for the non-invasive detection of bladder cancer that has been analytically validated as a tool with the potential to help clinicians manage patients at risk of harboring bladder cancer.